Goat Enterprise / James... [et al] - James, James; Jembau, Lily; Malie, Senian (2011)
At present, the prospect of goats in the livestock industry is very bright as the high demand for this commodity more than the amount that can be supplied in the domestic market and is increasing from year to year. But today has become a commercial industry that will bring returns and profits if they are supervised, managed with good as well as help and advice on an ongoing basis from the government, especially the Veterinary Services Department (VSD).Based on a very high confidence in this, then my group to prepare a livestock project Jamnapari in Mukah, Sarawak. This business plan is prepare to obtain financing in the amount RM400 000, to begin work on site preparation and modification, equipment purchases, and to cover expenses in the first year of operations. The approved financing from the Bank Rakyat consist of 5% of the total borrowing. This debt will be retired within 10 years. Additional financing has already been secured in the form of (1) RM 60 000 from the Bank Rakyat and (2) RM125 000 from two investors